Patient‐reported acceptable symptom state does not reflect quadriceps symmetry 1 year after ACL reconstruction - Tomas Pineda; Nathan H. Varady; David Mazy; Christophe Jacquet; Julien Druel; Matthieu Ollivier (Knee Surgery, Sports Traumatology, Arthroscopy, 2026)
Abstract Purpose To quantify the agreement between achievement of the validated patient acceptable symptom state (PASS) thresholds for Knee injury and Osteoarthritis Outcome Score (KOOS) Sport and KOOS Quality of Life (QoL) and isokinetic quadriceps limb symmetry index (LSI) ≥ 90% in a prospective cohort undergoing primary anterior cruciate ligament reconstruction (ACLR), and to determine whether this agreement was modified by autograft type. Methods Ninety consecutive patients undergoing primary ACLR with systematic anterolateral augmentation were prospectively allocated to three autograft groups in cohorts of 30: rectus femoris (RF), quadriceps tendon (QT) and hamstrings (HS). At 12 months postoperatively, all patients underwent concentric isokinetic testing at 60°/s and completed the KOOS Sport and Recreation and KOOS QoL subscales. Concordance between PASS achievement (KOOS Sport ≥75; KOOS QoL ≥62.5) and quadriceps LSI ≥ 90% was analysed using Cohen's kappa with bootstrap 95% confidence intervals and McNemar exact test. Results Agreement between PASS achievement and isokinetic quadriceps symmetry was absent: KOOS Sport versus LSI κ = 0.060 (95% confidence interval [CI] −0.071 to 0.191; McNemar p < 0.001); KOOS QoL versus LSI κ = 0.030 (95% CI −0.062 to 0.122; McNemar p < 0.001). Forty‐two patients (46.7%) met the KOOS Sport PASS threshold while showing LSI < 90%, compared with only five patients who achieved quadriceps LSI ≥ 90% without meeting the KOOS Sport PASS threshold. Among patients who reached the KOOS Sport PASS threshold, 76% had concurrent quadriceps LSI scores below 90%. The pattern was consistent across the three autograft groups (RF 50%, QT 47%, HS 43%; χ 2 p = 0.875). Conclusion PASS achievement and isokinetic quadriceps symmetry capture distinct dimensions of recovery 1 year after ACLR. The two assessments diverged in approximately half of the cohort, and this discordance was independent of autograft type. Patient‐reported and objective measures should be regarded as complementary rather than interchangeable, and a satisfactory PROM result alone should not be taken as evidence of restored quadriceps symmetry. Level of Evidence Level II, prospective comparative study.